IMPLEMENTASI PENDIDIKAN POLITIK DALAM MEMBANGUN KESADARAN POLITIK GENERASI MUDA PADA KARANG TARUNA NYAWIJI DI KELURAHAN KETELAN TAHUN 2025 - Ratri Pramesti Widyastuti, Ratri Pramesti; ., Sutoyo; Farida Sari, Ama (Prodi PPKn Universitas Slamet Riyadi, 2025)
This study aims to find out the implementation of political education in Karang Taruna Nyawiji Ketelan Village as well as to find out the obstacles, supporting factors, and challenges faced in building political awareness of the younger generation. Using qualitative descriptive methods, this study involves interviews, observations, and documentation as data collection techniques. The results of the study show that political education is implemented through various activities, but there are still obstacles such as lack of interest from members. In addition, the Nyawiji Youth Organization also plays an important role in increasing the political awareness of the younger generation.